(untitled) (Third Sector Social Economic Review, 2025)
Although Syrians who came to Turkey were initially considered as "guests", their prolonged stay of over a decade without returning to their home country indicates that they have moved beyond this temporary status. In order to sustain their lives in Turkey, Syrians have entered the labour market, which constitutes a significant step toward structural integration. However, the perspectives and experiences of host employers and the host community regarding this development are also crucial for successful integration. This study focused on the thoughts of host employers and the host community concerning Syrians’ participation in the labour market, which is a fundamental aspect of their structural integration process. In the literature, there are numerous theses that examine the opinions of local employers and the native population regarding Syrians’ involvement in the workforce. Based on an analysis of such theses, this research conducts a content analysis to offer a broader perspective on the issue. A total of 31 theses containing field data on the perspectives of local workers and the native population regarding Syrians’ participation in employment were selected as the units of content analysis. The results indicate that Syrians have entered the workforce across various sectors, with a significant proportion working informally. The primary reasons Syrians are preferred in the Turkish labour market include their status as cheap labour and their willingness to occupy positions typically avoided by the local population.